Effect of Dates (Phoenix Dactilyfera L) on Male Infertility - Semalina Wahyudi; R.A. Retno Ekowati; Andi Rinaldi (Althea Medical Journal, 2015)
Background: Infertility can be caused by prolonged use of paracetamol that leads to a decrease in the sperm concentration, motility, and morphology. Dates (Phoenix Dactilyfera L) have natural antioxidant effects through several mechanisms, such as neutralizing free radicals, against NO, OH, and H2O2, and also preventing lipid peroxidation. This study aimed to investigate the effect of dates on sperm concentration, motility, and morphology. Methods: An experimental study was conducted in the Laboratory of Cell Biology Department, Faculty of Medicine, Universitas Padjadjaran, during October–November 2012. Twenty two infertile male wistar rats were divided randomly into 2 groups. Group A was given 72 mg paracetamol/rat/day orally and group B was given 72 mg paracetamol/rat/day orally and 80% dates infusion/rat/day orally for 28 days and on the 29th day, sperm concentration, motility, and morphology were measured. Results were analyzed using unpaired t-testor Mann Whitney test. Result: In the control group, 502.73(100.66) sperm concentrations were compared to 397.55(143.07) in the treatment group. However, the sperm concentration mean in the treatment group was not significantly decreased (p>0.05) compared to the control group. The percentage of progressive sperm motility in the treatment group increased significantly compared to the control group. Meanwhile, the percentage of nonprogressive immotal sperm morphology was not significantly decreased. The percentage of normal sperm in the treatment group increased significantly (p<0.05) than the control group, while the percentage of abnormal sperm in the treatment group decreased significantly (p<0.05) compared to the control group. Conclusion: The dates affect sperm motility and morphology of infertile rats.Keywords: Dates, infertility, paracetamol, sperm DOI: 10.15850/amj.v2n1.437